Gut microbiota-dependent trimethylamine n-oxide pathway contributes to the bidirectional relationship between intestinal inflammation and periodontitis - Wang, Qiqi; Sun, Yue; Zhou, Tianyu; Jiang, Cong; A, Lan; Xu, Wenzhou (Frontiers in Cellular and Infection Microbiology, 2023)
Intestinal inflammation and periodontitis influence the development of each other through the bidirectional relationship. Trimethylamine-N-oxide (TMAO), a metabolite of the gut microbiota, could contribute to chronic inflammation in the gut by influencing the gut microbial composition and intestinal immunity. Clinical findings in patients with experimental periodontitis are often accompanied by an increasing in circulating TMAO levels. However, the role of TMAO in the bidirectional relationship between intestinal inflammation and periodontitis remains unclear. Thus, we explored whether TMAO influences the periodontitis process by affecting intestinal immunity and microbial composition in this article. Periodontitis was induced by unilateral ligation of the first molar in mice, and DMB was used as an inhibitor to reduce TMAO circulating. Twenty-five BALB/c mice were randomly divided into five study groups (n = 5/group): no periodontitis with DMB (Control group), periodontitis (P) group, periodontitis with TMAO (P+TMAO) group, periodontitis with TMAO and DMB (P+TMAO+DMB) group, and periodontitis with DMB (P+DMB) group. The effect of TMAO was determined by assessing changes in intestinal histology, intestinal flora composition, periodontal tissue, and periodontal pro-inflammatory factors at 10 days. The results showed that a significant increase in the severity of intestinal inflammation, a decrease in intestinal flora diversity, and an increase in the number of Firmicutes and the ratio of Firmicutes/Bacteroidetes in the P+TMAO group. In addition, the degree of periodontal tissue inflammation and alveolar bone resorption was more severe in the P+TMAO group than in other groups. Immunohistochemistry showed higher levels of TGF-β and IL-1β expression in the periodontal tissues of P+TMAO. Our data suggest that TMAO could influence periodontal immunity and promote periodontal inflammation by affecting the intestinal microenvironment, revealing TMAO may affect the development of periodontitis through the bidirectional relationship of the oral-gut axis.